THE DEVELOPMENT OF ENGLISH LANGUAGE TEACHING (ELT) COMPETENCY-BASED SYLLABUS IN SENIOR HIGH SCHOOL - Besral, Besral (Institut Agama Islam Negeri Imam Bonjol Padang, 2012)
Although competency has long been the major concern in ELT either in the EFL or ESL contexts, the rise of competency-based syllabus launched by the Ministry of National Education (2006) brought about significant issue among the English teachers in the country. One of the crucial issues is that how to transfer the concepts of competences into the syllabus design.Â Since a syllabus does not only contain a list of subject content, but also how curriculum planners (teachers) reflect their understanding and belief about nature of language and of language teaching and learning, the ELT must be carried out to achieve communicative competence. Current investigation on the practices of ELT, however, indicates that English teachers are still walking in place, leaving the CC as a big slogan in their jobs.